Pregunta
upstudy study bank question image url

Three consecutive terms of a geometric series are given in terms of a constant \( x \). \( U_{3}=(x+5), U_{4}=(4 x-1) \) and \( U_{5}=(2 x+3) \). Find the sum to infinity of the series. (Correct to four significant figures).

Ask by Vaughan Bond. in Ghana
Feb 15,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The sum to infinity of the series is 6.075.

Solución

We are given that three consecutive terms of a geometric series are   U₃ = x + 5   U₄ = 4x − 1   U₅ = 2x + 3 Since they are consecutive terms, they must share the same common ratio r. Thus   r = U₄/U₃ = (4x − 1)/(x + 5)   r = U₅/U₄ = (2x + 3)/(4x − 1) Equate these two expressions for r:   (4x − 1)/(x + 5) = (2x + 3)/(4x − 1) Cross-multiply to obtain:   (4x − 1)² = (x + 5)(2x + 3) Step 1. Expand each side:   Left side: (4x − 1)² = 16x² − 8x + 1   Right side: (x + 5)(2x + 3) = 2x² + 13x + 15 Step 2. Set the equation:   16x² − 8x + 1 = 2x² + 13x + 15 Step 3. Bring all terms to one side:   16x² − 8x + 1 − 2x² − 13x − 15 = 0   14x² − 21x − 14 = 0 Step 4. Divide the entire equation by 7 to simplify:   2x² − 3x − 2 = 0 Step 5. Solve the quadratic equation using the quadratic formula, where a = 2, b = −3, c = −2:   x = [−(−3) ± √((−3)² − 4·2·(−2)] / (2·2)   x = [3 ± √(9 + 16)] / 4   x = [3 ± √25] / 4   x = [3 ± 5] / 4 Thus, the two solutions are:   x = (3 + 5)/4 = 8/4 = 2   x = (3 − 5)/4 = (−2)/4 = −0.5 We must now choose the value of x that gives a valid geometric series (i.e. one that converges so that the sum to infinity exists). Calculate the common ratio r for each x: • For x = 2:   r = (4x − 1)/(x + 5) = (8 − 1)/(2 + 5) = 7/7 = 1   A geometric series with r = 1 does not converge (unless all terms are zero), so this case is not acceptable. • For x = −0.5:   r = (4(−0.5) − 1)/(−0.5 + 5) = (−2 − 1)/(4.5) = (−3)/4.5 = −2/3 Since |r| = 2/3 < 1, the series converges. Now, we are asked to find the sum to infinity of the series. The sum to infinity of a convergent geometric series is given by   S∞ = U₁/(1 − r) However, we are given U₃, not U₁. Since U₃ is the third term, and in a geometric series U₃ = U₁·r², we can solve for U₁:   U₁ = U₃ / r² For x = −0.5:   U₃ = x + 5 = (−0.5) + 5 = 4.5   r = −2/3, so r² = (−2/3)² = 4/9 Thus,   U₁ = 4.5 / (4/9) = 4.5 × (9/4) = 40.5/4 = 10.125 Now, calculate the sum to infinity:   S∞ = U₁ / (1 − r) = 10.125 / (1 − (−2/3))       = 10.125 / (1 + 2/3)       = 10.125 / (5/3)       = 10.125 × (3/5)       = 30.375/5       = 6.075 Rounded to four significant figures, the sum to infinity is 6.075. Thus, the answer is 6.075.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve for the sum to infinity of the geometric series given the terms \( U_{3}=(x+5), U_{4}=(4x-1) \), and \( U_{5}=(2x+3) \), we first need to find the common ratio \( r \) of the series. The common ratio \( r \) can be found using the formula for consecutive terms in a geometric series, given by: \[ r = \frac{U_{n+1}}{U_n} \] Thus, we can set up the following equations from our terms: 1. From \( U_3 \) and \( U_4 \): \[ r = \frac{U_4}{U_3} = \frac{4x - 1}{x + 5} \] 2. From \( U_4 \) and \( U_5 \): \[ r = \frac{U_5}{U_4} = \frac{2x + 3}{4x - 1} \] Setting these two expressions for \( r \) equal gives us the equation: \[ \frac{4x - 1}{x + 5} = \frac{2x + 3}{4x - 1} \] Cross-multiplying yields: \[ (4x - 1)^2 = (2x + 3)(x + 5) \] Expanding both sides: \[ 16x^2 - 8x + 1 = 2x^2 + 10x + 3x + 15 = 2x^2 + 13x + 15 \] Bringing all terms to one side results in: \[ 16x^2 - 8x + 1 - 2x^2 - 13x - 15 = 0 \] \[ 14x^2 - 21x - 14 = 0 \] Dividing the entire equation by 7 simplifies it: \[ 2x^2 - 3x - 2 = 0 \] Now we can factor this quadratic: \[ (2x + 1)(x - 2) = 0 \] Thus, we have two possible solutions: \[ x = -\frac{1}{2} \quad \text{or} \quad x = 2 \] Next, we need to calculate \( U_3, U_4, U_5 \) to determine the value of the common ratio \( r \) for valid \( x \). 1. If \( x = 2 \): \[ U_3 = 2 + 5 = 7, \quad U_4 = 4(2) - 1 = 7, \quad U_5 = 2(2) + 3 = 7 \] The ratio is: \[ r = \frac{7}{7} = 1 \] The series would not converge, so we discard this solution. 2. If \( x = -\frac{1}{2} \): \[ U_3 = -\frac{1}{2} + 5 = \frac{9}{2}, \quad U_4 = 4(-\frac{1}{2}) - 1 = -3, \quad U_5 = 2(-\frac{1}{2}) + 3 = 2 \] The ratio becomes: \[ r = \frac{U_4}{U_3} = \frac{-3}{\frac{9}{2}} = -\frac{6}{9} = -\frac{2}{3} \] To find the sum to infinity of a geometric series, the formula is: \[ S_{\infty} = \frac{U_3}{1 - r} \] Where \( r \) must be less than 1 in absolute terms: \[ S_{\infty} = \frac{\frac{9}{2}}{1 - (-\frac{2}{3})} = \frac{\frac{9}{2}}{1 + \frac{2}{3}} = \frac{\frac{9}{2}}{\frac{5}{3}} = \frac{9}{2} \times \frac{3}{5} = \frac{27}{10} = 2.7 \] Final answer: \[ \boxed{2.700} \] (to four significant figures).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad